Puleo, Alicia H., ed. (2020). Ser Feministas. Pensamiento y acción. Ilustrações de Verónica Perales. Madrid: Ediciones Cátedra. (Feminismos 30 años) - Emonts , Anne Martina (CEM – Cultura, Espaço & Memória, 2023)
DOI: https://doi.org/10.21747/2182-1097/cem15r3